Instructor's Effectiveness and Their Work Commitment in a Vocational College in China - Sun, Yaping (Pacific International Journal, 2024)
This study examines instructor effectiveness and work commitment at Shandong College of Economics and Business. Using a qualitative approach, semi-structured interviews were conducted with instructors to explore their experiences, perceptions, and strategies related to teaching effectiveness and work commitment. The findings reveal several key themes. In terms of teaching effectiveness, instructors emphasized the importance of dedication to student learning, adaptability in teaching methods, and subject matter expertise. Factors such as student engagement and active learning were identified as influential. Regarding work commitment, instructors were motivated by personal fulfillment, professional growth, and a supportive work environment. Strategies for enhancing work commitment included continuous professional development and building positive relationships with students. The implications of the findings suggest that the college should prioritize providing professional development opportunities, foster a supportive work environment, and promote student engagement. These findings contribute to understanding instructor effectiveness and work commitment, offering insights for improving teaching and learning environments in similar educational institutions.